Risk factors and predictive markers of post-stroke cognitive decline–A mini review - Guo, Xiaofan; Phan, Cattien; Batarseh, Sanad; Wei, Miao; Dye, Justin (Frontiers in Aging Neuroscience, 2024)
Stroke is one of the top causes of death and disability worldwide. Cognitive impairments are found in more than 70% of individuals who have survived a stroke. Cognitive decline is a major contributor to disability, dependency, and morbidity. The prevalence and severity of dementia vary depending on different characteristics of the stroke and other clinical risk factors. Here we discuss the effects of stroke territory, patients' age, sex, cerebral blood flow, acute reperfusion therapy, and cognitive reserve of post-stroke cognitive decline. Potential predictive molecular and genetic biomarkers of post-stroke cognitive impairments are also discussed.